(untitled) (Experimental biology, 2016)
The article describes the evaluation of some biochemical indices of muscle of juvenile sterlet (Acipenser ruthenus) and hybrid (Acipenser baeri × Acipenser gueldenstaedtii), grown on the basis of Kapshagai Spawning and Nursery Farm (Almaty region Enbekshikazakh region) at artificial feeding: OT-6 (control), "Domestic experimental feed for sturgeon", developed by the staff of the Kazakh Scientific Research Institute of Processing and Food Industries and feed for juvenile sturgeon Dutch firm "Coppens". In the course of the experiment found that using the Dutch food contributed to the increase of mass fraction of protein in the muscle tissue of juveniles on average by 23% over the entire period of the experiment, all the samples of muscle tissue of juvenile sterlet and hybrid glucose was less than 1%, the use of Dutch forage in the ration of sterlet increased lipid content in the muscle tissue in 1.7 times, and hybrid 1.6 times in comparison with control (OT- 6).